Phase separation in amorphous hydrophobically modified starch–sucrose blends: Glass transition, matrix dynamics and phase behavior. (1st November 2018) - Hughes, David J.; Bönisch, Gabriela Badolato; Zwick, Thomas; Schäfer, Christian; Tedeschi, Concetta; Leuenberger, Bruno; Martini, Francesca; Mencarini, Giacomo; Geppi, Marco; Alam, M. Ashraf; Ubbink, Job
Graphical abstract: Highlights: Amorphous–amorphous phase separation is observed for modified starch–sucrose blends. Double glass transition ( T g ) and mobile compounds induce dynamic phase behavior. T g of sucrose-rich phase impacts T g of the starch-rich phase via water migration. Quantitative phase model based on a glass transition temperature ( T g ) master curve. The current findings explain many stability phenomena in food and pharmaceutics. Abstract: The phase behavior and matrix dynamics of amorphous blends of octenyl succinic anhydride (OSA) modified starch and sucrose was studied as function of blend composition and water content. Phase separation into two amorphous phases, one enriched in OSA starch and the other in sucrose, was confirmed by differential scanning calorimetry (DSC). DSC and 1 H solid-state NMR show that the phase separation is only partial. The glass transition temperature ( T g ) of the OSA starch-rich phase was found to be ∼30–100 K higher than the T g of the sucrose-rich phase, depending on blend composition and water content. A novel type of coupling between changes in physical state of the sucrose-rich phase and plasticizer redistribution is proposed, leading to an unexpected increase of the glass transition temperature of the modified starch-rich phase at higher matrix water contents. A quantitative model for the phase separation of the anhydrous blends into two amorphous phases is presented. The model predicts that, with increasing blend sucrose content, the weight fraction of the sucrose-rich phase decreases, while the sucrose content of both the OSA starch-rich phase and the sucrose-rich phase increases. This novel phenomenon is relevant in the understanding of the stability and performance of multiphase food and pharmaceutical components.